The Rights to Religious Freedom for Adherents Faith in Indonesia: Comparative Study of the Rights to Religious Freedom in Asia - Shuhufi, Muhammad; W.W. Mamonto, Moch Andry; Buana, Andika Prawira; Fatmawati (International Journal of Criminology and Sociology, 2022)
Indeed, the dimension of rights that are basic is free to believe in trust; one of the beliefs in Indonesia that is still alive is Towani Tolotang. In connection with the study used a socio-legal study that focuses on descriptive-fundamental and comparative research methods, while the approach used is the historical approach, case approach, and comparison approach. Towani Tolotang's belief which is different from other faiths in Indonesia that are recognized by the state, should have the same right argued on the philosophical basis of the first principle of Pancasila "God Almighty", the constitutional basis of the 1945 Constitution Article 28 "Freedom of belief," and strengthened with Decision of the Constitution Court No. 97/ PUU-XIV /2016. In the Japanese context, there are similarities with Indonesia related to traditional beliefs such as the Shinto that lives to this day, and their existence is protected by the state through the policy that the state does not deal with matters of religion through the Japanese constitution. It is different from Malaysia which does not recognize traditional beliefs, but in the context of the protection of trust, it is regulated in the Federal Constitution of Malaysia that unfortunately, besides being Sunni Islam, security is not essential or limited to administrative protection.